The responsibility of the Head of State for the implementation of the authorized administrative judgment - Badran, Duaa Mohammed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2018)
The study dealt with the responsibility of the Head of State for the implementation of the authoritative judicial judgment. The administrative judgments issued against the administration are characterized by the specificity of the implementation as they relate to the administration, which is the authority of the authority and the state and the public order portfolio, which may deviate from the legality and do not comply with the implementation of administrative judgments. Here, the implementation of these provisions must be ensured through the identification of a responsible authority that can be relied upon to ensure implementation, which is represented by the head of state as responsible for the interests of the people and the supreme head of the executive authority.